Perception of battered women on power asymmetry in their couples and its relation to violence: a preliminary study - Megías, Jesús L.; Montañés, Pilar (Anales de Psicología / Annals of Psychology, 2012)
The main aim of this preliminary study was to explore if Power and Gender model by Pratto and Walker (2004) constitutes an adequate theoretical tool for the analysis of dyadic power and violence against women in couples. According to this model, power differences between genders are built upon four bases: resources control, social obligations, sexist ideology and threat or use of force. Sixty four battered women were interviewed and asked to express their perceptions about her and his partner’s power in three of these four bases. They also informed the frequency of psychological, physical and sexual episodes suffered in these relationships. Results showed that women perceived less power than their batterers in the three bases; these bases also correlated among them and those who had more power in one base was also more powerful in the others. Resources control by him and social obligations distribution in the couple significantly predicted psychological violence, but batterers’ sexist ideology predicted physical violence. Finally, women gave different importance to the four power bases as obstacles when considering leaving her abusive partner. In conclusion, Power and Gender model should be investigated more in the field of intimate partner violence against women.